A Model for Selecting Theoretical Framework through Epistemology of Research Paradigms - Bunmi Isaiah Omodan (African Journal of Inter-Multidisciplinary Studies, 2022)
Despite the importance of a theoretical framework in research, researchers face several challenges when selecting a theoretical framework for their study among which are a lack of agreement as to what constitutes a theory, a lack of a single theoretical framework that applies to all social science research, and selection based on personal conviction and interest rather than on the suitability of the theory to the research problem and the paradigmatic orientation of the chosen theory, which takes account of the epistemological assumptions. This study, therefore, aims to develop a model capable of enhancing the researcher's knowledge towards selecting an appropriate theoretical framework. The article is conceptual and dependent on logical arguments by presenting four paradigms alongside their epistemological standpoints. I argued the epistemology of research paradigms and their theoretical lensing using conceptual analysis to analyse the concepts and make sense of them. The study concludes that hypothesis, statistical/mathematical postulations, projections via research questions, and models are better to underpin studies under the positivist/post-positivist paradigm. Descriptive and analytic theories are better used when working within the interpretive paradigm. While transformative paradigm is best to be underpinned within critical theory, postcolonial theories and postcolonial indigenous paradigms are dependent on Indigenous Knowledge System.